Construction of a novel aminofluorene-based ratiometric near-infrared fluorescence probe for detecting carboxylesterase activity in living cells - Li, Jun-Mei; Liu, Yan-Zhao; Lv, Xiao-Fang; Zhou, Ding-Heng; Zhang, Hong; Chen, Yu-Jin; Li, Kun (Analytical methods, 2024)
Herein, we constructed a novel aminofluorene-based fluorescence probe ( FEN-CE ) for the detection of carboxylesterase (CE) in living cells by a ratiometric near-infrared (NIR) fluorescence signal. FEN-CE with NIR emission (650 nm) could be hydrolyzed specifically by CE and transformed to FENH with the release of the self-immolative group, which exhibited a red-shifted emission peak of 680 nm. In addition, FEN-CE showed high selectivity for CE and was successfully used in the detection of CE activity in living cells through its ratiometric NIR fluorescence signals. Herein, we constructed a novel aminofluorene-based fluorescence probe ( FEN-CE ) for the detection of carboxylesterase (CE) in living cells by a ratiometric near-infrared (NIR) fluorescence signal.